Evidence that normative beliefs is a multidimensional construct: personal and mass media referents - Zolait, A.H.S.; Sulaiman, A. (2008)
While Theory of Reasoned Action (TRA) is commonly used to model normative beliefs that depend on human referents, this study extends the normative belief to allow modelling the mass media referents and linking them to both Subjective Norm (SN) and behaviourol intention (BI). This study emphasizes the importance of communication channels influence (referents). Rogers' theory introduces two types of referents, mass media and interpersonal referents. This study used factor analysis to validate the factorability of normative beliefs and prove that the external normative beliefs sourced by both media and personal referents represent valuable factors in explaining 54% of the variation in norms that in turn. used as determinant of BI to use the Internet banking.